Analysis Of Leadership Style Application And Motivation By Managers In Improving Housekeeping Employees Performance At Bumi Senyiur Hotel Samarinda - Satria Nurhidayat, Dhanin (Jurnal Syntax Fusion, 2022)
Hotel Bumi Senyiur Samarinda is one of the 5 star hotels in Samarinda. The right leadership style and motivation can influence employees so that they can improve employee performance adequately. This study aims to determine the application of leadership styles and motivation by housekeeping managers in improving employee performance at the Bumi Senyiur Hotel. The object of this research is Bumi Senyiur Hotel. This study uses qualitative descriptive research by conducting a series of data collection in the form of interviews, observations, and documentation so that the results will be quite clear. The results of this qualitative descriptive study are the leadership style used by housekeeping managers at the Bumi Senyiur Hotel using a paternalistic leadership style, where a leader will make decisions according to deliberation but the decision remains absolute in the hands of a leader and a manager also embraces employees like a father. The motivation used is positive motivation and the method used is the direct motivation method where employees will get rewards and facilities in order to support work. So that the leadership style and motivation applied by the manager really results in good employee performance